A 400‐year isotopic record of seabird response to eastern tropical Pacific productivity. Issue 2 (28th September 2015) - Conroy, Jessica L; Collins, Aaron F; Overpeck, Jonathan T; Bush, Mark B; Cole, Julia E; Anderson, David J
Abstract : Seabirds play an important role in coastal environments, serving as key indicators of marine ecosystem variability as well as biovectors that influence terrestrial productivity and carbon storage. Long‐term estimates of seabird populations remain rare, but lakes that support large seabird populations in their watersheds can archive a history of seabird activity in their sediment records. Here we present a seabird guano‐influenced sediment record from Genovesa Crater Lake, Galápagos Islands, home to the world's largest reported colony of red‐footed boobies ( Sula sula ) and smaller populations of other species. Influx of seabird guano into Genovesa Crater Lake produces high sedimentary δ 15 N values, and temporal variability in sediment δ 15 N primarily reflects changes in guano influx through time. Two abrupt increases in sedimentary δ 15 N occurred at 1835 AD and 1965 AD, and variance increased following the 1965 AD shift. The largest of these abrupt shifts at 1835 AD coincided, within age model error, with an abrupt increase in marine productivity indicators in sediment records off the coast of Perú and Chile. In the latter part of the twentieth century, δ 15 N values increased during periods of higher landings of Peruvian anchoveta and sardines. We hypothesise that seabird presence and activity on Genovesa increased during periods of higher regional marine productivity. Enhanced variance in Genovesa δ 15 N following the 1965 AD shift may reflect a modern population more susceptible to climate and environmental variability than at any other time in the last 400 years. Abstract : Learning from Guano in search of a Paleo Seabird Proxy